(untitled) (Research, Society and Development, 2020)
The use of resistant starch in new food products is increasing due to the health benefits associated with fiber intake. However, its use in products such as pasta is limited because it weakens the gluten network. One way to solve this problem is by adding enzyme transglutaminase into the formulation. The objective of this study was to evaluate the influence of resistant starch (RS) and transglutaminase (TG) on spaghetti cooking characteristics, texture, color and protein solubility using a central composite rotational design of two independent variables (x1 = RS 0 to 20 %; x2 = TG 0.2 to 1.0 %). The main dependent variables studied were resistant starch, instrumental color, cooking and texture characteristics and protein solubility. The results were analyzed using Response Surface Methodology, which demonstrated that RS and TG influenced the product quality, being statistically significant (p<0.10) for the color, optimum cooking time, weight and volume increase, elasticity and content resistant starch. The luminosity (L*) was higher with the increase in RS and TG. Higher levels of RS decrease cooking time and elasticity. Among the independent variables, RS presented the greatest effect on the dependent variables studied. The optimal point (0.70 of desirability) requires the use of 18.65 % resistant starch, resulting in a spaghetti with appeal of source in dietary fiber, as they contain more than 2.5 g of dietary fiber, per serving, in the product ready for consumption.